PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA GURU DIMODERASI KEPEMIMPINAN KEPALA SEKOLAH (Studi Pada MTs Swasta Kecamatan Winong Kabupaten Pati) - Muhamad Anis, 12.5202.0227; Sutomo, Y (Jurnal Mahasiswa Pasca Sarjana, 2016)
This study aimed to examine the effect of Competence and Motivation on TeacherPerformance moderated Principal Leadership (Studies in Teacher Private MTs Winong Districtof Pati regency). This study included in the quantitative research using survey method throughdescriptive analysis approach. This study whit a census tehnic where the sample size is equal tothe population of as many as 115 teachers, while the data is processed as many as 102 teachers.Measurements using a Likert scale with 5 (five) alternative answers. Test instruments used arevalidity and reliability. Normality Test (1 Sample-KS) Classical Assumption Test (testheterokedastisitas) The test model used is the coefficient of determination (R2) and the F test(Goodness of Fit). Test this hypothesis using regression analysis. Based on the results of thestudy can be summarized as follows: (i) Competence positive and significant impact on teacherperformance, (ii) Motivation positive and significant impact on teacher performance, (iii)Leadership Principal positive and significant impact on teacher performance, (iv) EffectCompetence of the Teacher Performance is not moderated Leadership Principal, (iv) Effect ofMotivation on teacher performance is not moderated Leadership PrincipalKeywords : Competence, Motivation, Leadership Principal and Teacher Performance